Marge in charge and the missing orangutan - Fisher, Isla, 1976- (Fisher, Isla, 1976- Marge in charge, 2019)
"Marge, the rainbow-haired babysitter, returns! This tiny duchess has a trip planned for Jakey and Jemima Button--and she's going to break a lot of rules along the way. In these three hilarious stories, a trip to the zoo with Marge seems like a perfect adventure. But it might turn out to be a perfect disaster! When Jakey's tooth goes missing, a train gets stopped by a ferocious beast, and a favorite orangutan can't be found, it seems as if everything will be ruined. But if there's one thing Jakey and Jemima know, it's that even disasters are fun when Marge is in charge!"--From publisher's website.